Implications on feedstock processing and safety issues for semi-batch operations in supercritical water gasification of biomass - De Blasio, Cataldo (2021)
Biomass with a large amount of moisture is well-suited to be processed by supercritical water gasification, SCWG. The precipitation of inorganics, together with char formation and repolymerization, can cause reactor plugging and stop the process operations. When plugging occurs, sudden injections of relatively large mass quantities take place, influencing the mass flow dynamics significantly in the process. Reactor plugging is a phenomenon very well observed during SCWG of industrial feedstock, which hinders scale-up initiatives, and it is seldom studied with precision in the literature. The present study provides an accurate evaluation of continuous tubular reactor dynamics in the event of sudden injections of water. An interpretation of the results regarding water properties at supercritical conditions contributes to comprehending mass and heat transfer when plugging occurs. Experiments are then compared to SCWG of a biomass sample aiming to give key insights into heat transfer and fluid dynamics mechanisms that could help develop operational and control strategies to increase the reliability of SCWG. In addition, a simplified model is presented to assess the effect of material integrity on burst-event likelihood, which states that SCWG is safe to operate, at 250 bar and 610◦ C, in tubular reactors made of 0.22 wall thickness-to-diameter ratio Inconel-625 with superficial microfractures smaller than 30 µm. We also suggest improvement opportunities for the safety of SCWG in continuous operation mode.